Isolation and biochemical characterization of two soluble iron(III) reductases from Paracoccus denitrificans - Mazoch, Jirí; Tesarík, Radek; Sedlácek, Vojtech; Kucera, Igor; Turánek, Jaroslav (European journal of biochemistry, 2004)
Two soluble enzymes (FerA and FerB) catalyzing the reduction of a number of iron(III) complexes by NADH, were purified to near homogeneity from the aerobically grown iron-limited culture of Paracoccus denitrificans using a combination of anion-exchange chromatography (Sepharose Q), chromatofocusing (Mono P), and gel permeation chromatography (Superose 12). FerA is a monomer with a molecular mass of 19 kDa, whereas FerB exhibited a molecular mass of about 55 kDa and consists of probably two identical subunits. FerA can be classified as an NADH:flavin oxidoreductase with a sequential reaction mechanism. It requires the addition of FMN or riboflavin for activity on Fe(III) substrates. In these reactions, the apparent substrate specificity of FerA seems to stem exclusively from different chemical reactivities of Fe(III) compounds with the free reduced flavin produced by the enzyme. Observations on reducibility of Fe(III) chelated by vicinal dihydroxy ligands support the view that FerA takes part in releasing iron from the catechol type siderophores synthesized by P. denitrificans. Contrary to FerA, the purified FerB contains a noncovalently bound redox-active FAD coenzyme, can utilize NADPH in place of NADH, does not reduce free FMN at an appreciable rate, and gives a ping-pong type kinetic pattern with NADH and Fe(III)-nitrilotriacetate as substrates. FerB is able to reduce chromate, in agreement with the fact that its N-terminus bears a homology to the previously described chromate reductase from Pseudomonas putida. Besides this, it also readily reduces quinones like ubiquinone-0 (Q0) or unsubstituted p-benzoquinone.
Keywords: FMN-reduktasa; Electrophoresis, Polyacrylamide Gel; Catalysis; Kinetics; FMN Reductase; sekvenční homologie aminokyselin; Sequence Homology, Amino Acid; katalýza; chromatografie iontoměničová; sekvence aminokyselin; Paracoccus denitrificans; Molecular Sequence Data; Anion Exchange Resins; Solubility; rozpustnost; Amino Acid Sequence; hmotnostní spektrometrie; molekulární sekvence - údaje; molekulová hmotnost; Mass Spectrometry; Isoenzymes; Molecular Weight; aniontoměniče; elektroforéza v polyakrylamidovém gelu; Chromatography, Ion Exchange; kinetika; izoenzymy